Exploring factors affecting gender inequality in the completion of higher education in India: a survival model analysis - Singh, R; Mukherjee, P; Kumar, A (Young Lives, 2023)
This report uses longitudinal data from Young Lives to explore gender differentials in dropout rates before completing higher education among 26-year-old young adults in Andhra Pradesh and Telangana, India. Using detailed modelling, it finds that young women have a significantly higher risk of dropping out before completing higher education than young men. Furthermore, individual, household and educational factors perpetuate gender inequity in higher education completion, with young adults from disadvantaged social groups and households in the bottom wealth tercile being more likely to drop out than their counterparts. The authors also find that even as young as age 12, indicators such doing paid work and domestic chores, as well as having low cognitive scores, are positively associated with a higher risk of non-completion of secondary school, demonstrating the negative affect of early risks on long-term trajectories. The authors conclude that as the Indian National Education Policy 2020 seeks to achieve gender balance in educational opportunities, these findings are an immensely valuable contribution to policy influencing. This report forms part of a body of research by Young Lives into gender, skills and education. To read more about this, visit our webpage here and for latest updates, follow up on social media.